PTSD and Suicidal Behaviors Amongst L'Aquila 2009 Earthquake Young Survivors - Claudia Carmassi; Carlo Antonio Bertelloni; Valerio Dell'Oste; Chiara Luperini; Chiara Luperini; Donatella Marazziti; Rodolfo Rossi; Liliana Dell'Osso (Frontiers Media S.A., 2021)
Background: Post-traumatic stress disorder (PTSD) is one of the most frequent and severe psychiatric consequences of natural disasters, frequently associated with suicidality. The aim of this study was at examining the possible relationships between suicidal behaviors and full-blown or partial PTSD, in a sample of young earthquake survivors. The second aim was at investigating the specific role of PTSD symptoms on suicidality.Methods: A total of 475 young adults who survived the L'Aquila 2009 earthquake, one of the most severe Italian disasters of the last decades, were recruited and assessed after 21 months from the catastrophe. Participants were evaluated by two questionnaires assessing subthreshold psychopathology, the Trauma and Loss Spectrum Self-Report (TALS-SR) to investigate both full and partial PTSD, and two specific Mood Spectrum Self-Report (MOODS-SR) sub-domains exploring suicidality, namely suicidal ideation and suicide attempts.Results: The ensuing findings showed that suicidal ideation and suicide attempts were present, respectively, in 40 (8.4%) and 11 (2.3%) survivors. Rates of suicidal ideation were significantly more elevated in full-blown PTSD subjects (group 1), as compared with those suffering from partial (group 2) or no PTSD (group 3). Interestingly, group 2 subjects showed significantly more suicidal ideation than healthy individuals, and less than those of group 1, while the frequency of suicide attempts was similar across the three groups. Suicidal ideation was associated with higher scores in the following TALS-SR domains: grief-reactions, re-experiencing, avoidance and numbing, maladaptive coping, and personal characteristics/risk factor.Conclusions: The results of the present study support and extend previous findings on the role of PTSD symptoms in suicidality after a severe earthquake. However, as compared with available literature, they also highlight the significant impact of sub-threshold PTSD manifestations in increasing the suicide risk in survivors of a mass disaster.